The Impact of UPOV 1991 on Plant Variety Protection and Agricultural Innovation: Comparing Case Studies of Singapore and Japan - Andi Faradilla Ayu Lestari; Siti Subeqiyatun Attitoh; Aulia Rahmatin Masyhuri; Resti Nurfitriyani; Rizqi Sari Dewi Girsang; Junyta Iswari Adhiwidya (Journal of World Trade Studies, 2024)
This article aims to analyze the comparative implementation of UPOV 1991 as a form of international compliance and its impact in Singapore and Japan. The findings of this research reveal that Singapore ratified UPOV 1991 in 2004 and implemented it in the Plant Varieties Protection Act 2004. Meanwhile, Japan ratified UPOV 1991 in 1998 and implemented it in the amendments to the Plant Variety Protection and Seed Act 1978. It provides a 25-year protection guarantee for plant breeders, and the adoption of UPOV 1991 also has various other impacts on Singapore and Japan. Singapore has made notable strides in the agricultural innovation sector and is more actively involved in international cooperation addressing developing effective plant variety protection systems. As for Japan, a more efficient framework for the use of IPR, which increases the competitiveness of domestic agriculture, has been established, and innovation in plant variety testing technology continues to experience advancements that bring numerous benefits to local farmers.